On eigenvalues and equivalent transformation of trigonometric matrices - Lin, Zhiping (2013)
This paper discusses some issues related to trigonometric matrices arising from the design of finite impulse response (FIR) digital filters. A conjecture on the eigenvalues of a trigonometric matrix is posed with a partial proof given. A new result is also presented on the related equivalent transformation of this trigonometric matrix into a diagonal matrix.